The Effect of Competitive Exercises Using Physical Performance Tracking Technology (GPS Playertek Plus and Polar H9) on Developing Speed in Iraqi Premier League Football Players - Kadhim, Haitham; Hussain, Mohammed; Fathi, Maab (Journal of Physical Education, 2024)
Football is one of the most important team sports, practiced by men and women, young and old, across various age groups. The physical development in this sport can be attributed to athletic training and modern technology, which have contributed significantly to advancing the sports field in general. Outstanding performance in football requires precise and quick physical abilities, closely tied to the competitive nature of the game. Speed is fundamental in football, making the use of technologies such as GPS tracking devices and heart rate monitors essential in both training and matches. This study aims to develop the speed of Al-Talaba SC players in Baghdad using a scientifically-based approach to improve their performance. The importance of the study lies in introducing competitive exercises with the help of global tracking technologies to enhance performance during training and develop training strategies based on scientific data. The research highlights a physical weakness in speed among the players, which calls for the use of the GPS Playertek Plus tracking device to improve speed. The scientific approach helps in analyzing data, designing competitive training sessions, and achieving optimal performance in matches. The study indicates that competitive exercises based on GPS tracking devices positively impact the development of player speed, reinforcing the importance of using these technologies in sports training, such as GPS tracking devices, to enhance player speed and design appropriate exercises for each player.